Examples of Deductive Proofs
Lemma 2. For any well-formed formula B, ~~B→ B.
Proof. We shall construct a proof in L of ~~B → B.
1. | (~ B → ~~B) → ((~B → B)) → B) | Instance of Axiom A3 by Substituting ~B for A in Axiom A3. |
2. | ~B → ~B | By Lemma 1. |
3. | (~B → B)) → B | By Corollary II. |
4. | ~~B → (~B → ~~B) | Instance of Axiom A1 by substituting ~~B for A and ~B for B in Axiom A1. |
5. | ~~B → B | From 3 and 4 by hypothetical syllogism - Corollary I. |
So, we have
~~B → B
And by applying the Deduction Theorem, we get
~~B → B
Therefore, for any well-formed formula B, (~~B → B) is theorem of L.
This completes the proof.
Lemma 3. For any well-formed formula B, B → ~~B.
Proof. We shall construct a proof in L of B → ~~B.
1. | (~~~B → ~B) → ((~~~B → B) → ~~B) | Instance of Axiom 3 by Substituting ~~B for B and B for A in the Axiom 3. |
2. | ~~~B → B | By Lemma 2. |
3. | (~~~B → B) → ~~B | From 1 and 2 by modus ponens. |
4. | B → (~~~B → B) | Instance of Axiom A1 by substituting ~~~B for B and B for A in Axiom A1. |
5. | B → ~~B | Form 3 and 4 by hypothetical syllogism - Corollary I. |
So, we have
B → ~~B
And by applying the Deduction Theorem, we get
B → ~~B
Therefore, for any well-formed formula B, (B → ~~B) is theorem of L.
This completes the proof.
Lemma 4. For any well-formed formulas A and B, ~A → (A → B).
Proof. We shall construct a proof in L of ~A → (A → B).
1. | ~A | Hypothesis. |
2. | A | Hypothesis. |
3. | ~A → (~B → A) | Instance of Axiom A1 by substituting ~B for B in Axiom A1. |
4. | ~A → (~B → ~A) | Instance of Axiom by substituting ~A for A and ~B for B in Axiom A1. |
5. | ~B → A | From 2 and 3 by modus ponens. |
6. | ~B → ~A | From 1 and 4 by modus ponens. |
7. | (~B → ~A) → ((~B → A) → B) | Axiom A3. |
8. | (~B → A) → B | From 6 and 7 by modus ponens. |
9. | B | From 5 and 8 by modus ponens. |
Thus, by proof (i.e. lines 1-9)
~A, A B
Applying the Deduction Theorem, we have
~A A → B
And apply the Deduction Theorem one more time and we get
~A → (A → B)
Therefore, for any well-formed formula A and B, ~A → (A → B) is theorem of L.
And this completes the proof.
Let us swap the variable in the Lemma 4 and see what happens. [Well its not difficult to see what will happen. By the rule of substitution nothing will happen and we will get the same thing but we will do any way.]
Lemma 4a. For any well-formed formulas A and B, ~B → (B → A).
Proof. We shall construct a proof in L of ~B → (B → A).
1. | ~B | Hypothesis. |
2. | B | Hypothesis. |
3. | ~B → (~A → B) | Instance of Axiom A1 by substituting B for A and ~A for B in Axiom A1. |
4. | ~B → (~A → ~B) | Instance of Axiom by substituting ~B for A and ~A for B in Axiom A1. |
5. | ~A → B | From 2 and 3 by modus ponens. |
6. | ~A → ~B | From 1 and 4 by modus ponens. |
7. | (~A → ~B) → ((~A → B) → A) | Instance of Axiom 3 by substituting A for B and B for A in Axiom A3. |
8. | (~B → A) → B | From 6 and 7 by modus ponens. |
9. | B | From 5 and 8 by modus ponens. |
Thus, by proof (i.e. lines 1-9)
~B, B A
Applying the Deduction Theorem, we have
~B B → A
And apply the Deduction Theorem one more time and we get
~B → (B → A)
Therefore, for any well-formed formula A and B, ~B → (B → A) is theorem of L as expected.
And this completes the proof.
Lemma 5. For any well-formed formulas A and B, (~B → ~A) → (A → B).
Proof. We shall construct a proof in L of (~B → ~A) → (A → B).
1. | (~B → ~A) | Hypothesis. |
2. | A | Hypothesis. |
3. | (~B → ~A) → ((~B → A) → B) | Axiom 3. |
4. | A → (~B → A) | Instance of Axiom 1 by substituting ~B for B in Axiom 1. |
5. | (~B → A) → B | From 1 and 3 by modus ponens. |
6. | A → B | From 4 and 5 by hypothetical syllogism. |
7. | B | From 2 and 6 by modus ponens. |
Thus, by proof (i.e. lines 1-7), we have
(~B → ~A), A B
Applying the Deduction Theorem, we have
(~B → ~A) (A → B)
Apply the Deduction Theorem one more time to get
(~B → ~A) → (A → B)
Therefore, for any well-formed formula A and B, (~B → ~A) → (A → B) is theorem of L.
And this completes the proof.
Lemma 6. For any well-formed formulas A and B, (A → B) → (~B → ~A).
Proof. We shall construct a proof in L of (A → B) → (~B → ~A).
1. | A → B | Hypothesis. |
2. | ~~A → A | By Lemma 2 (above). |
3. | ~~B → B | From 1 and 2 by hypothetical syllogism i.e., Corollary I. |
4. | B → ~~B | By Lemma 2 (above). |
5. | ~~A → ~~B | From 3 and 4 by hypothetical syllogism i.e., Corollary I. |
6. | (~~A → ~~B) → (~B → ~A) | By Lemma 5 (above). |
7. | ~B → ~A | From 6 and 7 by modus ponens. |
Thus, by proof (i.e. lines 1 through 7), we have
A → B ~B → ~A
Applying the Deduction Theorem, we get
A B → (~B → ~A)
Apply the Deduction Theorem again and we have
(A → B) → (~B → ~A)
Therefore, for any well-formed formula A and B, (A → B) → (~B → ~A) is theorem of L.
And this completes the proof.
Lemma 7. For any well-formed formulas A and B, A → (~B → ~(A →B))
Proof.
Clearly, by modus ponens, we have
A, A → B B
Applying the Deduction Theorem, we get
A (A → B) → B
Once again, apply the Deduction Theorem and we have
A → (A → B) → B _________________ (1)
From Lemma 6, we have
(A → B) → (~B → ~A)
Get a instance of Lemma 6 by substituting (A → B) for A.
((A → B) → B) → (~B → ~(A → B)) _________________ (2)
Now apply hypothetical syllogism (Corallary I) to (1) and (2), we get
A → (~B → ~(A → B))
And this is what was to be shown.
This completes the proof.
Lemma 8. For any well-formed formulas A and B, (A → B) → ((~A → B) → B).
Proof. We shall construct a proof in L of (A → B) → ((~A → B) → B).
1. | A → B | Hypothesis. |
2. | ~A → B | Hypothesis. |
3. | (A → B) → (~B → ~A) | By Lemma 6. |
4. | ~B → ~A | From 1 and 3 by modus ponens. |
5. | (~A → B) → (~B → ~~A) | Instance of Lemma 6 by substituting ~A for A in Lemma 6. |
6. | ~B → ~~A | From 2 and 5 by modus ponens. |
7. | (~B → ~~A) → ((~B → ~A) → B) | Instance of Axiom A3 by substituting ~A for A in Axiom A3. |
8. | (~B → ~A) → B | From 6 and 7 by modus ponens. |
9. | B | Form 4 and 8 by modus ponens. |
Thus, by proof (i.e., lines 1 through 9), we have
A → B, ~A → B B
Apply the Deduction Theorem, we get
A → B (~A → B) → B
Apply the Deduction Theorem one more time
(A → B) → ((~A → B) → B)
Therefore, for any well-formed formula A and B, (A → B) → ((~A → B) → B) is theorem of L.
And this completes the proof.
------------------------------------------------------------------------------------------------